Internalization of Economic Education through Family Financial Management of Fishermen of Prigi Beach Watulimo Trenggalek East Java - Erlina Puspita Istikomah; Wening Patmi Rahayu; Ludi Wishnu Wardana (Journal of Educational Analytics, 2023)
The aim of this research is to describe the internalization of economic education in fishing families at Prigi Beach, Tasikmadu Village, Watulimo District, Trenggalek Regency through family financial management. The research used qualitative methods with 12 respondents who live in Tasikmadu Village. The results of the research show that in financial management fishing families do not record income and income, budget and make shopping lists. Deliberation with your partner is carried out to decide on mutual needs and prioritize needs over desires. When income increases, fishermen tend to realize needs that have been postponed, invest in jewelry and land, and save independently. The internalization of economic education in fishing families is mostly carried out by example through real practice in production and consumption activities, verbal explanations in the form of advice, as well as behavioral demands that are relevant to economic topics and open to the family's financial condition. Pocket money is a learning medium to provide confidence in managing children's money, advise children in determining their personal needs, teach them to save and set aside pocket money, and teach children discipline in carrying out consumption activities, such as asking permission.